2012
DOI: 10.1179/1743290111y.0000000016
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of particle size for water atomised metal powders: parameter study

Abstract: This work aims to investigate how some significant atomising parameters influence the mass median particle size d 50 of water atomised metal powders. More specifically, these were water pressure, melt flowrate, water jet angle, liquid metal viscosity and surface tension. Existing models for the prediction of d 50 during water atomisation were reviewed. The selected models were fitted and compared with atomising experiments of liquid iron containing 0?5-4?4%C. Experimental results and model calculations were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 16 publications
2
14
0
Order By: Relevance
“…The magnitude of the pressure exponent 0.94 in Equation ( 2) compares well with values reported by others [3,6,8,14] which range between 0.6 and 1.2. The standard deviation SD, which represents the dispersion of the particle size distribution, does not change significantly with water pressure.…”
Section: Effect Of Water Pressure P Wsupporting
confidence: 88%
“…The magnitude of the pressure exponent 0.94 in Equation ( 2) compares well with values reported by others [3,6,8,14] which range between 0.6 and 1.2. The standard deviation SD, which represents the dispersion of the particle size distribution, does not change significantly with water pressure.…”
Section: Effect Of Water Pressure P Wsupporting
confidence: 88%
“…Recently, a parameter study of d 50 particle size indicated that the viscosity has a stronger influence than the surface tension for water atomized metal powders. [7] Quested et al pointed out the relevance of the experimental values of the surface tension and density to spray forming. This study included a mathematical description of the high temperature atomisation process and the influence of the oxygen and sulfur steel concentration on the surface tension in the experimental trials was mentioned.…”
mentioning
confidence: 99%
“…23) This model is presented in Eq. (13), with calculated exponents relevant for the present study ............. (13) where k is a model constant, α is the jet angle between the axis of the water jet and axis of the metal stream, DM is the melt stream diameter in m, mW and mM is the mass flow rate of water and metal respectively in kg s -1 .…”
Section: D50 Modelmentioning
confidence: 99%